2015
DOI: 10.3892/or.2015.3719
|View full text |Cite
|
Sign up to set email alerts
|

(+)-Terrein inhibits human hepatoma Bel-7402 proliferation through cell cycle arrest

Abstract: Hepatoma is a common malignant tumor. Thus, the development of a high‑efficacy therapeutic drug for hepatoma is required. In this study, (+)‑terrein isolated from the marine sponge‑derived Aspergillus terreus PF‑26 against cell growth, apoptosis and cell cycle were assessed by MTT and flow cytometry. mRNA array containing 73 cell cycle‑related genes and three cell morphology‑related genes was generated and its performance evaluated. The cell cycle pathway map was created using the pathview package. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…[ 3 ] PCNA, an essential DNA replication protein, was a cellular marker of cell multiplication. [ 30 ] CCND2 related to the cell cycle was also one of the cellular markers of cell proliferation. In the current study, forskolin treatment for 10 days downregulated the expression levels of CYP19A1, PCNA , and CCND2 , whereas it increased the expression of PTGFR ‐ and steroidogenesis‐related gene ( StAR, HSD3B , and P450scc ) and P 4 production, which was consistent with previous report, indicating the luteinization of goat GCs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] PCNA, an essential DNA replication protein, was a cellular marker of cell multiplication. [ 30 ] CCND2 related to the cell cycle was also one of the cellular markers of cell proliferation. In the current study, forskolin treatment for 10 days downregulated the expression levels of CYP19A1, PCNA , and CCND2 , whereas it increased the expression of PTGFR ‐ and steroidogenesis‐related gene ( StAR, HSD3B , and P450scc ) and P 4 production, which was consistent with previous report, indicating the luteinization of goat GCs.…”
Section: Discussionmentioning
confidence: 99%
“…Terrein exhibits several biological activities including anti-inflammation, anti-melanogenesis, and anticancer properties. Treatment of keratinocytes, hepatoma and lung cell lines with terrein does not stimulate apoptosis (7,8), instead it appears to limit proliferation by promoting cell cycle arrest. Similarly, terrein also inhibited growth and induced cell cycle arrest in a human ovarian cancer cell line (9) and hepatoma Bel-7402 cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of keratinocytes, hepatoma and lung cell lines with terrein does not stimulate apoptosis (7,8), instead it appears to limit proliferation by promoting cell cycle arrest. Similarly, terrein also inhibited growth and induced cell cycle arrest in a human ovarian cancer cell line (9) and hepatoma Bel-7402 cells (8). However, the activity of terrein is cell type-dependent and this compound not only inhibits cell proliferation but also induces apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that terrein has antiproliferative activity in a number of types of cancer (20)(21)(22)24). Cancer is an uncontrolled cell proliferation and death (12); therefore, inhibiting specific proteins that drive the cell cycle may be an efficient strategy to develop novel anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Terrein may also inhibit cell proliferation and induce cell cycle arrest in human ovarian cancer cells (23). More recently, it has been revealed that terrein inhibited Bel-7402 human hepatoma cell proliferation through cell cycle arrest (24).…”
Section: Introductionmentioning
confidence: 99%